Analisis Kepatuhan Wajib Pajak Kendaraan Bermotor dalam upaya Meningkatkan Penerimaan Pajak Daerah pada Kantor Bersama Samsat Jakarta Timur Tahun 2015-2018 - Abharina Avidaniar Bintary (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
This study aims to determine the compliance of motor vehicle taxpayers and to find out the obstacles, stimulus, and strategies that are carried out in increasing local tax revenues in East Jakarta’s One Roof System (Samsat). The research method is a Qualitative approach with descriptive research type. The results of the study on Compliance in East Jakarta Samsat are fairly good, this is supported by indicators from research such as good registration because taxpayers have followed and know the procedures well, the reports carried out by East Jakarta samsat are in accordance with the specified schedule, Payment of taxpayers in Samsat is fairly good with increasing taxpayers obeying each year in 2018 the highest percentage of compliant taxpayers reaching 60% with taxpayers totaling 1,296,666 but arrears in tax payable in East Jakarta are quite high in 2017 the amount of arrears from Taxes Motorized vehicles reached Rp. 90,568,276,707, - however, the realization of motor vehicle tax revenues has reached its target each year. Obstacles to the existence of taxpayers are not compliant because Taxpayers' awareness is still lacking due to busyness causing negligence and forgetting to carry out tax obligations and online payment processes are constrained by the lack of understanding of taxpayers about E-Samsat, while other obstacles are due to Taxpayer Data which is not appropriate, taxpayers who postpone payment of tax fines are waiting for the elimination of administrative fines so that the efforts made by East Jakarta Samsat provide strict sanctions to taxpayers who do not pay motor vehicle tax, provide taxpayers in paying taxes, and carry out programs elimination of administrative fines